Siglec-G controls the severity of chronic lymphocytic leukemia - Röder, Bettina; Fahnenstiel, Hannah; Seifert, M.; Schäfer, Simon; Winkler, Thomas; Nitschke, Lars (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

The inhibitory receptor Siglec-G controls the severity of chronic lymphocytic leukemia - Röder, Bettina; Fahnenstiel, Hannah; Schäfer, Simon; Budeus, Bettina; Dampmann, Maria; Eichhorn, Melanie; Angermüller, Sieglinde; Brost, Christa; Winkler, Thomas; Seifert, Marc; Nitschke, Lars (EMBO Reports, 2023)
Chronic Lymphocytic Leukemia (CLL) is the most common leukemia in adults in the Western world. B cell receptor (BCR) signaling is known to be crucial for the pathogenesis and maintenance of CLL cells which develop from mature CD5+ B cells. BCR signaling is regulated by the inhibitory co-receptor Siglec-G and Siglec-G-deficient mice have an enlarged CD5+ B1a cell population. Here, we determine how Siglec-G expression influences the severity of CLL. Our results show that Siglec-G deficiency leads to earlier onset and more severe course of the CLL-like disease in the murine Eμ-TCL1 model. In contrast, mice overexpressing Siglec-G on the B cell surface are almost completely protected from developing CLL-like disease. Furthermore, we observe a downmodulation of the human ortholog Siglec-10 from the surface of human CLL cells. These results demonstrate a critical role for Siglec-G in disease progression in mice, and suggest that a similar mechanism for Siglec-10 in human CLL may exist.
CRIS-Team Scopus Importer:2023-07-21
Keywords: BCR signaling; CLL; Siglec-10; Siglec-G overexpressing mice; Siglecs

The role of Siglec-G on B cells in autoimmune disease and leukemia - Röder, Bettina; Nitschke, Lars (Seminars in Arthritis and Rheumatism, 2023)
Background: B-cell activation is triggered by the B-cell receptor, but is also controlled by inhibitory receptors, which limit the BCR signaling. CD22 (Siglec-2) and Siglec-G are such inhibitory receptors expressed on B cells. CD22- or Siglec-G deficient mice show enhanced B cell activation. Objectives: It was the objective of our study to investigate the role of these inhibitory receptors in autoimmune disease and leukemia. Results: Ageing Siglec-G deficient or CD22 x Siglec-G deficient mice develop an SLE-like autoimmune disease with autoantibodies and kidney nephritis. In a mouse model for chronic lymphocytic leukemia (CLL), Siglec-G deficient mice show an earlier and more severe disease. Author's conclusions: These results show that Siglec-G and CD22 are both involved in preventing autoimmune diseases and leukemia delevopment and could therefore be attractive new targets.
CRIS-Team Scopus Importer:2023-12-08
Keywords: None